If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 11 = 53 Reorder the terms: 11 + 7x = 53 Solving 11 + 7x = 53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 7x = 53 + -11 Combine like terms: 11 + -11 = 0 0 + 7x = 53 + -11 7x = 53 + -11 Combine like terms: 53 + -11 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| 105=3(-6n-7) | | 3=j/6-2 | | -8-2(3x-3)= | | 2x+8+x=-14+3x+22 | | 7p+1=15 | | -1+3+n=-2+5 | | 26-8p=19-7p | | 3(2x+9)=33 | | 6z-8z=z+5+3z | | 4x+10=x+4 | | -31+4+y=-4+8 | | 2z+6-4z-3=5z+12 | | 11=2x-7 | | 94-2x=25x+16 | | 7f+50=120 | | 2((m/4)-4)=16 | | 14x+14=3x+8 | | 1/2y+1/3y=1/2-13 | | 2z+64z-3=5z+12 | | 8x-49=95-4x | | -4y+18=2+3y | | 2a-7/5+2=a | | 2z^2x-z^3=1 | | 15=4x-8 | | -30-6=8s-10s-7s | | -7a=28 | | 4y+18=2+3y | | 9-(2x-1)=8-3x | | 4-22=n-4+13 | | -1/3x=-5 | | 6+6x=56-x | | 9(-2+x)=-63 |